PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION PADA POKOK BAHASAN ATURAN SINUS DAN COSINUS - Reyka Nasrul (Departemen Matematika, 2020)
The purpose of this research is to develop a learning tools in the form of a student worksheet based on the Team Assisted Individualization type of cooperative model on the material of the rules of sines and cosinus for students grade X SHS that are valid and practical. By using the Plomp model, this development research consists of three stage namely the Preliminary Research, the Development or Prhotyping Phase and the Assesment Phase. Based on the results of the validity data analysis, it shows that the student worksheet based on the Team Assisted Individualization model on the material of the sine and cosine rules in terms of content feasibility, the Team Assisted Individualization type cooperative model, language, presentation and graphics have a valdity level of 83.66% with very valid categories. This student worksheet also met the practical criteria of the student response questionnaire results with a percentage of 88.88%. Based on these results, it can be concluded that the student worksheet based on the Team Assisted Individualization type cooperative model on the material of the rules of sines and cosines for class X SMA students can be declared valid and practical. Keywords— Development Research, Student Worksheet, Team Assisted Individualization